Strengthening the impact and value of international marketing curriculum Outcomes: A comparative study of Turkish and European business students perceptions of coursework and careers - (:unkn) unknown (My University, 2010)
Tremendous growth in the internationalization of businesses over the past decade has been fueled by numerous factors (market saturation, growing demand, etc.). With this growth, there is a need to expand business school curricula, placing more importance on international studies than in the past. This has been emphasized by the American Assembly of Collegiate Schools of Business (AACSB) as being a priority for accredited colleges of business. The real driver of these changes is the fact that regardless of size, more and more firms are moving into international markets. This expansion requires an intensive recruitment of marketing graduates from business schools. Given the increasing demand for marketing professionals who have an understanding and appreciation for the significance of international markets, it is imperative that innovative international marketing curricula be developed. The purpose of this study was to examine the perceptions of business school students regarding international marketing courses and careers. A comparative study of Turkish and Northern European (NE) students' perceptions towards international marketing courses and international marketing careers was conducted. Results of the study indicated significant differences between Turkish and Northern European students regarding their perceptions of international marketing both in terms of course work and careers. Turkish students in this study perceived international marketing courses as being exciting, trendy and providing opportunities leading to better job opportunities and better salaries. In contrast, the Northern European students perceived international marketing courses as a 'natural' required course for marketing majors and not providing any specific better job opportunities or salaries. Turkish students also perceived international marketing careers in general more prestigious than did the Northern European students. Different perceptions of students belonging to different countries may be linked to the distinct cultural orientations of these two countries. However it may also be linked to the international marketing curriculum that is being offered.